Membrane destabilization by Gramicidin S: evaluating its compatibility with cryoprotective protocols - Perepelitsa, Ihor; Berest, Volodymyr (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2025)
Probl Cryobiol Cryomed 2025; 35(4):242